Certain Families of Holomorphic and Sălăgean Type Bi-Univalent Functions Defined by (p,q)-Lucas Polynomials Involving a Modified Sigmoid Activation Function - Ramadhan, Ali Mohammed; Ali Jiben Al-Ziadi , and Najah (JOURNAL OF ADVANCES IN MATHEMATICS, 2022)
The aim of the present paper is to introduce a certain families of holomorphic and Sălăgean type bi-univalent functions by making use (p, q) - Lucas polynomials involving the modified sigmoid activation function Φ(δ)=z/(1+e-δ) δ>=1 in the open unit disk Λ. For functions belonging to these subclasses, we obtain upper bounds for the second and third coefficients. Also, we debate Fekete-Szegö inequality for these families. Further, we point out several certain special cases for our results.